Pendeteksian Fraud oleh Auditor: Peran Pengalaman Audit, Kualitas Audit, dan Tekanan Waktu - Rifani, Riza Amalia; Hasan, Hamida (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This research aims to examine the influence of Audit Experience, Audit Quality, and Time Pressure on Auditor's Ability to Detect Fraud in Public Accounting Firms in East Jakarta. The research employs a quantitative approach, analyzed using panel data with the SPSS software. The study's population consists of Public Accounting Firms in the Makassar region, with a sample of 32 active auditors working in these firms. Data collection was done using primary data by distributing questionnaires directly to Public Accounting Firms in the Makassar region. The research findings indicate that (1) Audit Experience has an impact on Fraud Detection Ability, (2) Audit Quality influences Fraud Detection Ability, and (3) Time Pressure affects Fraud Detection Ability in Public Accounting Firms in the Makassar region. These results confirm that audit experience, audit quality, and time pressure play a significant role in detecting fraud during an audit.